2013
DOI: 10.1007/s12034-013-0542-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of new polyimide/clay nanocomposite films

Abstract: A series of polymer-clay nanocomposite (PCN) materials consisting of polyimide and typical clay were prepared by solution dispersion. Quaternary alkylammonium modified montmorillonite, Cloisite 20A, was used as organoclay. Poly(amic acid) solution was prepared from the reaction of benzophenone-4,4 ,3,3-tetracarboxylic dianhydride and 2-(5-(3,5-diaminophenyl)-1,3,4-oxadiazole-2-yl) pyridine in dimethylacetamide. Thermal imidization was performed on poly(amic acid)/organoclay dispersion in a regular temperature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The decrease of solvent uptake by clay/polyimide nanocomposite was also reported by Mansoori et al [21]. They suggested that there is a strong interaction between polyimide and montmorillonite and the excellent barrier properties of the large aspect ratio silicate, which enhanced the available surface area of the fillers.…”
Section: Solvent Uptake Study Of Neat Nylon 66 and Clay/nylon 66 Nasupporting
confidence: 73%
“…The decrease of solvent uptake by clay/polyimide nanocomposite was also reported by Mansoori et al [21]. They suggested that there is a strong interaction between polyimide and montmorillonite and the excellent barrier properties of the large aspect ratio silicate, which enhanced the available surface area of the fillers.…”
Section: Solvent Uptake Study Of Neat Nylon 66 and Clay/nylon 66 Nasupporting
confidence: 73%
“…In addition, the presence of nitrogen atoms in pyridine rings can generate polarized bonds, which increase the solubility of polymers due to the intermolecular dipole-dipole interactions in a polymer-solvent system [41,42,43]. For example, PIs derived from 2-(5-(3,5-diaminophenyl)-1,3,4-oxadiazole-2-yl)pyridine [44] and 1,3-bis(5-amino-2-pyridinoxy)benzene [45] have all have been demonstrated to own high solubility and thermal properties. Li et al [46] reported a class of cardo-type polyimides with cyclopentyl-containing alicyclic units as side groups.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the well-known brittleness, the common detrimental property of cured bismaleimides owing to the high cross linking densities, these materials are having several advantageous properties like excellent thermal stability, long shelf life, low moisture absorption, excellent adhesion, low dielectric constant and several acceptable physico mechanical properties. 10,11 The fine tuning of the thermal properties of bismaleimide matrix resin is possible through the modification of the structural entities present in between the maleimide groups. 12 The aromatic structure is thermally stable compared to the aliphatic structure.…”
Section: Introductionmentioning
confidence: 99%